The role of alpha-synuclein in synucleinopathy: Impact on lipid regulation at mitochondria–ER membranes - Peter A. Barbuti; Cristina Guardia-Laguarta; Taekyung Yun; Zena K. Chatila; Xena Flowers; Chantel Wong; Bruno F. R. Santos; Simone B. Larsen; James S. Lotti; Nobutaka Hattori; Elizabeth Bradshaw; Ulf Dettmer; et al. (npj Parkinson's Disease)
Abstract The protein alpha-synuclein (αSyn) plays a pivotal role in the pathogenesis of synucleinopathies, including Parkinson’s disease and multiple system atrophy, with growing evidence indicating that lipid dyshomeostasis is a key phenotype in these neurodegenerative disorders. Previously, we identified that αSyn localizes, at least in part, to mitochondria-associated endoplasmic reticulum membranes (MAMs), which are transient functional domains containing proteins that regulate lipid metabolism, including the de novo synthesis of phosphatidylserine. In the present study, we analyzed the lipid composition of postmortem human samples, focusing on the substantia nigra pars compacta of Parkinson’s disease and controls, as well as three less affected brain regions of Parkinson’s donors. To further assess synucleinopathy-related lipidome alterations, similar analyses were performed on the striatum of multiple system atrophy cases. Our data reveal region- and disease-specific changes in the levels of lipid species. Specifically, our data revealed alterations in the levels of specific phosphatidylserine species in brain areas most affected in Parkinson’s disease. Some of these alterations, albeit to a lesser degree, are also observed in multiple system atrophy. Using induced pluripotent stem cell-derived neurons, we show that αSyn regulates phosphatidylserine metabolism at MAM domains, and that αSyn dosage parallels the perturbation in phosphatidylserine levels. These findings support the notion that αSyn pathophysiology is linked to the dysregulation of lipid homeostasis, which may contribute to the vulnerability of specific brain regions in synucleinopathy. These findings have significant therapeutic implications.